Analisis Destination Branding dan Diferensiasi Wisata Alam Gosari dalam Meningkatkan Daya Saing Destinasi Wisata di Kabupaten Gresik - Asrorul Fitri As Tsani; Agus Solikhin; Sugiman Sugiman (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
Competition among tourist destinations demands a strong identity, while Gosari Nature Tourism (WAGOS) in Gosari Village, Ujungpangkah, possesses natural potential, a history dating back to the Majapahit era, and local culture that have not yet been fully utilized as its primary identity. This study aims to analyze destination branding strategies and destination differentiation through natural uniqueness, history, and the empowerment of local communities, as well as the roles of both in enhancing WAGOS’s competitiveness. The study employs a descriptive qualitative approach using interviews, observations, and document analysis, analyzed using the Miles and Huberman model through data reduction, presentation, and conclusion-drawing. The results show that WAGOS possesses two destination identities nature tourism and historical tourism but branding remains dominated by natural aspects, meaning that historical and cultural potential has not been optimally utilized. Differentiation is achieved through the integration of a flower garden with the landscape of a former mining site, as well as the involvement of MSMEs, Karang Taruna, and PKK, thereby ensuring that the community reaps economic benefits. It is concluded that the integration of destination branding and differentiation based on historical and natural assets, as well as local empowerment, is a key factor in strengthening the competitiveness of tourist destinations, and this constitutes the novelty of this study.